HUBUNGAN JUMLAH HEMATOKRIT DAN TROMBOSIT DENGAN DERAJAT KEPARAHAN PASIEN INFEKSI DENGUE DI RSUD DR. M. HAULUSSY AMBON PERIODE 2019 - Meilisa Meita Kusdianto; Elpira Asmin; Vina Z. Latuconsina (PAMERI, 2020)
Dengue infection is an infection caused by the dengue virus and is transmitted through the bite of aedes aegypti female mosquito. Platelets and hematocrit are important parameters in the treatment of dengue infection patients. Proper diagnosis of the stage and condition of sufferers of dengue infection is important to determine the prognosis. Platelet and hematocrit examinations for each degree of dengue infection clinic are expected to help in grouping and managing patients based on their clinical degree. This research aims to see the relationship between platelet and hematocrit examination results with the clinical degree of DHF based on WHO criteria. The purpose of this study was to determine the relationship of hematocrit and platelet counts with the severity of dengue infection patients in RSUD Dr. M. Haulussy ambon period 2019. This research is an analytic study using secondary data. Data collection using total sampling techniques in all patients with dengue infection period 2019. Samples in this study were 92 people. Hypothesis testing uses bivariate analysis with Spearman's nonparametric hypothesis, testing with SPSS software. The results found 51 women (55.4%) more than 41 men (44.6%). The results of the analysis by the Spearman correlation test on a combined sample and after being separated for a female sample obtained platelets associated with the clinical degree of dengue infection. Hematocrit associated with the clinical degree of dengue infection. In a male sample, platelets were found to be unrelated to the clinical degree of dengue infection. Hematocrit is not related to the clinical degree of dengue infection